Microbiology and technology of fermented foods - Hutkins, Robert W. (IFT Press, 2006)
In Microbiology and Technology of Fermented Foods, Robert Hutkins has written the first text on food fermentation microbiology in a generation. This authoritative volume also serves as a comprehensive and contemporary reference book. A brief history and evolution of microbiology and fermented foods, an overview of microorganisms involved in food fermentations, and their physiological and metabolic properties provide a foundation for the reader. How microorganisms are used to produce fermented foods and the development of a modern starter culture industry are also described. Successive chapters are devoted to the major fermented foods produced around the world with coverage including microbiological and technological features for manufacture of these foods: Cultured Dairy Products; Cheese; Meat Fermentation; Fermented Vegetables; Bread Fermentation; Beer Fermentation; Wine Fermentation; Vinegar Fermentation; Fermentation of Foods in the Orient.